COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BASED ON LIQUIDITY RATIO AND PROFITABILITY RATIO - Prie Dewi Listanti; Vira Aulia Gusfi; Ulul Azmi; Sri Hermuningsih (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the comparison of financial performance based on liquidity and profitability ratios. This research uses the Quantitative Descriptive method, namely by collecting, processing, analyzing and presenting data descriptively with samples of financial statements of PT. Indofood Sukses Makmur, Tbk (INDF) and PT. Mayora, Tbk (MYOR) in 2021-2022. From the analysis we have done, INDF and MYOR have no difficulty in paying off their short-term debt obligations. Profitability ratio of PT. Indofood Sukses Makmur, Tbk in 2020 to 2021 decreased and PT Mayora, Tbk in 2020 to 2021 increased, and in the calculation of ROA and ROE at PT. Indofood Sukses Makmur, Tbk showed a decrease in 2021–2022 while PT Mayora, Tbk experienced an increase. This means that there is an increase in management performance of PT Mayora, Tbk but there needs to be an increase in management performance at PT Indofood Sukses Makmur Tbk.